The Effectiveness of Pharmacist-led Education on Patient Adherence to Medication: A Literature Review - Fitri, Maghfiroti; Dewi, Rusmina Iswanti Kumala (Asosiasi Dosen Muda Indonesia, 2025)
Patient adherence to medication is a critical factor for the success of pharmacological therapy, yet low adherence remains a challenge in many healthcare systems. Pharmacist-led education has emerged as a promising strategy to improve medication adherence. This study aims to assess the effectiveness of pharmacist educational interventions on patient adherence through a literature review approach. A total of 19 national and international articles published in the last 10 years were reviewed. Findings indicate that interventions such as face-to-face counseling, educational booklets, SMS reminders, and training on proper medication use significantly enhance adherence, reduce the risk of complications, and improve patients’ quality of life. These results reinforce the strategic role of pharmacists in delivering patient-centered pharmaceutical care.